TECHNO-ECONOMIC ASSESSMENT OF A CHICKEN-MANURE-FED BIOGAS GENERATOR SYSTEM IN A PHILIPPINE FARM - Santos, Elisa; Pagdato, Ian (International Journal of Engineering Technologies and Management Research, 2025)
Chicken manure is an abundant agricultural waste stream capable of supporting decentralized biogas power systems. This study presents a techno-economic assessment of a 160 kW biogas generator operating on chicken-manure-derived biogas in a tropical Philippine farm. Using realistic but generic technical parameters, the system consumes approximately 90 Nm³/hr of biogas at 55% methane content and generates an estimated 1.27 gigawatt-hours (GWh) of electricity annually. Methane mitigation totals roughly 260,000 kg/year, equivalent to 6,500 tons of carbon dioxide equivalent (CO₂eq) using a Global Warming Potential over 100 years (GWP100) of 25. Diesel displacement exceeds 380,000 liters annually. With a capital cost of PHP 6.5 million and annual operating expenses of PHP 1.4 million, the system achieves net annual savings of approximately PHP 15 million, yielding a payback period of about five months and a Return on Investment (ROI) exceeding 200%. Findings demonstrate that chicken-manure-fed biogas generator systems offer strong technical, environmental, and economic benefits suitable for rural energy applications.